Parental knowledge about familial Mediterranean fever: a cross-sectional study - Yıldırım, Deniz Gezgin; Bakkaloğlu, Sevcan A; Soysal-Acar, A Şebnem; Buyan, Necla (The Turkish Journal of Pediatrics, 2021)
Background. The life-long course, long-term complications, necessity for regular treatment, and potential side effects of the medications must be well understood by parents of pediatric familial Mediterranean fever (FMF) patients. The aim of this study was to assess parental knowledge and to investigate how parents obtained scientific information about FMF. Methods. One hundred and seventy-one pediatric FMF patients and their parents were enrolled in this crosssectional study. Three-part questionnaires, including forms on socio-demographics, knowledge and perceptions of FMF, and how to get information about FMF, were administered to parents. Results. In the analysis of the knowledge questions, 90.1% of parents were aware of colchicine as an effective drug for FMF, but only 39.2% of them were aware that there is no vital risk during FMF attacks. Caregivers preferred to obtain information from physicians (98.8%), websites (47.9%), seminars (3.5%), and books (1.7%). The knowledge scores of parents were significantly higher among those whose children were using antiinterleukin- 1 therapy in addition to colchicine relative to those on colchicine alone (p = 0.04). There was a positive correlation between knowledge level and parental educational status (p = 0.0001). Conclusions. Knowledge scores among parents of pediatric FMF patients are unsatisfactory. The parents whose children have a severe disease course and a need for anti-interleukin-1 therapy are more knowledgeable. For parents, continuing education programs including books, seminars and web-sites giving information about the course, prognosis, complications and treatments of FMF should be employed immediately after the diagnosis and thereafter.
Keywords: childhood; familial Mediterranean fever; parental knowledge; pediatric rheumatology